Food security issues and challenges - Fillol Mazo, Adriana; Martín López, Miguel Angel (Food science and technology, 2021)
"It is clear that one of the most damaging global problems is hunger. There is still a high proportion of hungry people in the world, the number of human beings in this condition exceeding 690 million, according to the latest State of Food Security and Nutrition in the World Report (FAO 2020). Consequently, its eradication is extremely urgent. Nevertheless, it does not appear that Sustainable Development Goal number two, i.e. Zero Hunger, will be achieved by 2030. The United Nations itself admits this, stating that "the world is not on track to achieve Zero Hunger by 2030. If recent trends continue, the number of people affected by hunger would surpass 840 million by 2030". The problems facing food in the world today have increased considerably, as well as various factors and phenomena that augment the complexity of the issues or situations that fall within the scope of food security, such as: climate change, land grabbing, use of chemical fertilizers, loss of agrodiversity and other agricultural sustainability issues, obesity problems resulting from unhealthy diets, the impact of the coronavirus pandemic, the lack of justiciability of the right to food, the use of biotechnology in food, etc. In short, this book is a diverse compilation of the new manifestations of global food security seen from several angles and areas. The book aims to let visualize the main global problems and challenges that have a negative impact on food security, with the underlying objective of highlighting the need for reinforcing its full application in all contexts and countries. To this end, we believe that it is necessary to make its concept operational, and take it into consideration when applying policies and standards, especially in those areas and matters that may undermine said food security. In this sense, it is essential to strengthen its legal protection through a coherent and operational interpretation of the human right to food, so as to broaden its content and make it consistent with its pillars and foundations"--